Gambaran Kadar Kolesterol Total pada Pengguna Rokok Elektrik - Arisanti, Dewi; Basarang, Mujahidah; Rianto, Muh. Rifo; Rustiah, Waode; Bano, Siti Maryam (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
An electric cigarette is a tool that functions to convert chemical substances into the form of vapor and distributes them to the lungs using electricity. One of the harmful elements contained in cigarettes is nicotine. If nicotine circulates in the body, it stimulates the secretion of the adrenaline hormone resulting in an increase in heart rate, blood pressure and changes in fat metabolism. This study aims to describe cholesterol levels in e-cigarette users in Mamajang sub-district. This research is a laboratory observation which aims to describe cholesterol levels in e-cigarette users in Mamajang district. The number of samples used were 20 samples. The object of this research is the blood of electric smokers using the POCT method. From the results of research conducted on 20 samples. 6 of them got increased results and 14 samples got normal. So it can be concluded that of the 20 samples, 6 samples (74%) got normal results and 6 samples (26%) got increased results.